Flexible power‐point‐tracking‐based frequency regulation strategy for PV system. Issue 10 (9th June 2020) - Zhong, Cheng; Zhou, Yang; Zhang, Xiao‐Ping; Yan, Gangui
Abstract : This study proposes a novel frequency regulation strategy based on a power reserve control method. Unlike existing strategies, irradiance information and complex model estimation are not required, except for the maximum power curve. The suboptimal power point at any irradiance and reserve ratio can be automatically converged with the proposed tracking method. Furthermore, an adaptive step‐size tracking method is proposed to improve the output power fluctuation around the suboptimal power point. The simulation results with several scenarios are used to verify that the proposed strategy can quickly and robustly track a given power reserve ratio under the irradiance and reserve ratio variation conditions. The proposed strategy can significantly improve the frequency response of power systems with photovoltaic (PV) generation.